(untitled) (Konturen, 2020)
In Un Franco, 14 Pesetas (2004), Carlos Iglesias tells the story of Spanish migration to Central Europe during the 1960s through a fictional remembering of his family’s years as immigrants to Uzwil, in the Swiss eastern province of Toggenburg. His memories of the Swiss landscape, luminous, green, and open contrast with a grim, grey and enclosed Madrid, both origin and end of the six-year journey. This essay explores the interrelation between memory, space, and human mobility in Un Franco, 14 Pesetas. Through a journey of migration to Switzerland, Iglesias tells a story of return to Madrid, and unveils the contradictions of Spain’s so-called ‘economic miracle’ of the 1960s. Merging experiences of arrival and departure, presents and pasts, Iglesias’s film shows how immigration is rooted in space, and inseparable from economic, political and social processes that are historically specific.